2001
DOI: 10.1063/1.1389522
|View full text |Cite
|
Sign up to set email alerts
|

Electrical current distribution across a metal–insulator–metal structure during bistable switching

Abstract: Combining scanning electron microscopy (SEM) and electron-beam-induced current (EBIC) imaging with transport measurements, it is shown that the current flowing across a two-terminal oxide-based capacitor-like structure is preferentially confined in areas localized at defects. As the thin-film device switches between two different resistance states, the distribution and intensity of the current paths, appearing as bright spots, change. This implies that switching and memory effects are mainly determined by the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
106
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(111 citation statements)
references
References 30 publications
(42 reference statements)
1
106
1
Order By: Relevance
“…A confined current transport was also found by Yang et al in formed TiO 2 MIM-devices. 10,20 Furthermore, electron beam induced current measurements 21 on Pt/ SrZrO 3 / SRO structures have also shown that confined conduction paths exist below the metal electrode after the electroforming process. In epitaxial Sr 2 TiO 4 thin films, Shibuya et al 22 found another type of forming process which exhibits a "homogeneous" character and can be explained by a homogeneous distribution of the conducting filaments beneath the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…A confined current transport was also found by Yang et al in formed TiO 2 MIM-devices. 10,20 Furthermore, electron beam induced current measurements 21 on Pt/ SrZrO 3 / SRO structures have also shown that confined conduction paths exist below the metal electrode after the electroforming process. In epitaxial Sr 2 TiO 4 thin films, Shibuya et al 22 found another type of forming process which exhibits a "homogeneous" character and can be explained by a homogeneous distribution of the conducting filaments beneath the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…This in turn can be changed (write operation) and measured (read) when subjected to an electric field. The insulator layer is a nanometer-thick thin film, which can be composed of a wide variety of materials, such as binary oxides [8], perovskites [9][10][11][12], as well as many other compounds, which are known for their resistance switching properties [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…9 Recently, dielectric perovskite type oxides ͑ABO 3 ͒ have attracted increasing attention as candidates for resistive information storage. [10][11][12] Multilevel storage was demonstrated for Cr-doped SrZrO 3 structures. 10 Here, different resistance levels could be addressed by a variation of length and amplitude of the programming voltage pulse.…”
mentioning
confidence: 99%
“…There is still some debate about the physical mechanisms of the resistance change and about the key experimental parameters. Mechanisms under discussion are ͑i͒ trapping/detrapping effects and charge transfer processes via donor and acceptor levels ͑Cr 3+ /Cr 4+ ͒, 10,13 ͑ii͒ a Mott metal-insulator transition, 14 ͑iii͒ formation of local current domains, 12 ͑iv͒ redox processes of extended defects, 15 and ͑v͒ conductivity changes due to a reversal of a local spontaneous polarization. 16 Polarization changes might not be stringently of ferroelectric nature, but might also be due to defect dipoles, e.g., formed by acceptor/oxygen vacancy defect associates.…”
mentioning
confidence: 99%